The EXIT for Prenatally Diagnosed Cervical Cystic Teratoma: A Case Report - Sabri Cansaran; Ayşenur Cerrah Celayir; Serdar Moralıoğlu; Habibe Ayvacı; Semih Tuğrul; Fahri Ovalı; Handan Çetiner (EL-Med-Pub, 2015)
The Ex-utero intrapartum treatment (EXIT) is a procedure performed during caesarean section while on fetal-placental circulation. We present a prenatally diagnosed cervical cystic mass causing tracheal compression which was managed successfully with the EXIT procedure.